The Scholarly Transformation of Arabic Language and Literature at UIN KHAS Jember: An Analysis of Curriculum, Research, and Instructional Development: English - Sri Wahyuni; Rizki, Ahmad; Istiadah (Universitas Djuanda, 2026)
The academic transformation of the Arabic Language and Literature Study Program (BSA) at UIN KHAS Jember represents an effort to enhance the quality and relevance of Islamic higher education in the era of Merdeka Belajar (Freedom to Learn). This study focuses on analyzing the form and direction of transformation in curriculum development, teaching methods, and the strengthening of scientific disciplines. A descriptive qualitative approach was employed, supported by light quantitative data to achieve a comprehensive understanding. Data were collected through interviews, observations, questionnaires, and documentation studies, and analyzed using Miles and Huberman’s interactive model, which includes data reduction, presentation, and conclusion drawing. The findings reveal that the curriculum shift from KKNI to MBKM based on Outcome-Based Education (OBE) positively impacts learning effectiveness and graduate relevance to the job market. Students perceive the applied learning methods as participatory and contextual, while lecturers actively innovate in instructional media. Increased attention to local academic works enriches scholarly knowledge and cultural preservation. Thus, academic transformation in the BSA Program reflects adaptive, humanistic, and competency-oriented learning.